2023
DOI: 10.1186/s40352-023-00206-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Road to Mental Readiness (R2MR) training among correctional workers in Canada

Abstract: Background Mental health frameworks, best practices, and the well-being of public safety personnel in Canada are topics of increasing interest to both researchers and organizations. To protect and improve worker mental health, different training programs have been implemented to serve this population. The Road to Mental Readiness (R2MR) training regimen is one such program specialized to build cultural awareness of mental health, reduce stigma, and mitigate the cumulative impacts of exposures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Our research also confirms the tensions in many relationships with management ( McKendy et al, 2021 ) and the desire for improved mental health treatment options available to correctional workers ( Johnston et al, 2022b ), especially the desire to include some form of peer support ( Johnston et al, 2021 , 2022a ; Ricciardelli and Carleton, 2022 ). To this point, these findings reiterate the need to sensitize managers and leaders in correctional organizations to the importance of mental health and readiness (see Johnston et al, 2023 ) as well as finding other opportunities (i.e., through technology) to promote mental health awareness, resources, education, treatments, coping skills, work-stress management skills, and so forth to struggling correctional workers ( Paginin and Simbula, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our research also confirms the tensions in many relationships with management ( McKendy et al, 2021 ) and the desire for improved mental health treatment options available to correctional workers ( Johnston et al, 2022b ), especially the desire to include some form of peer support ( Johnston et al, 2021 , 2022a ; Ricciardelli and Carleton, 2022 ). To this point, these findings reiterate the need to sensitize managers and leaders in correctional organizations to the importance of mental health and readiness (see Johnston et al, 2023 ) as well as finding other opportunities (i.e., through technology) to promote mental health awareness, resources, education, treatments, coping skills, work-stress management skills, and so forth to struggling correctional workers ( Paginin and Simbula, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…Further, a cultural environment where discussions about mental health are normalized and in which correctional workers can openly turn to peers and peer supports may help to reduce stigma ( Johnston et al, 2022b , 2023 ). Relatedly, in their survey research of 118 healthcare professionals working for the Italian Health Authority, Paganin et al (2023) found an indirect effect of mental health leadership on teamwork through interpersonal conflict and cooperation, suggesting leadership training and frameworks can positively impact teamwork among workers, particularly amidst crises such as the COVID-19 pandemic (see also Franke et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resiliency training for public safety personnel is often used to facilitate help-seeking, primarily through reducing stigma (Krakauer et al, 2020). Results from a qualitative study assessing correctional workers’ perceptions of the Road to Mental Readiness (R2MR) training programme suggest that R2MR is effective in reducing stigma and increasing awareness of mental health issues (Johnston et al, 2023). Results from the qualitative study also highlighted the value of peer support and the need for safe, nonjudgemental spaces to discuss mental health issues in the workplace (Johnston et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Untuk mengatasi kesulitan kesehatan mental pekerja, perlu untuk memahami unsur-unsur yang mempengaruhi kesehatan mental di tempat kerja dan mengembangkan intervensi yang efektif (Holmes et al 2020;Albott et al 2020;Johnston et al 2023). Penelitian tentang kesehatan mental pekerja dapat memberikan pengetahuan yang lebih baik tentang masalah kesehatan mental di tempat kerja (Giorgi et al 2020;Fisher, Newton, and Sainsbury 2021;LaMontagne et al 2014).…”
Section: Pendahuluanunclassified
“…Untuk menjaga dan meningkatkan kesehatan mental pekerja, banyak program pelatihan telah dibuat. Rejimen pelatihan The Road to Mental Readiness (R2MR) adalah salah satu program yang dirancang untuk meningkatkan pengetahuan budaya personel keselamatan publik tentang kesehatan mental, mengurangi stigma, dan membatasi efek kumulatif dari paparan terhadap insiden yang berpotensi menimbulkan stres psikologis (Johnston et al 2023). Pentingnya kesehatan mental dan penanggulangan sebagai prasyarat bagi katalis TI untuk menginspirasi perilaku kerja inovatif di kalangan pekerja jarak jauh (Zaza et al 2023).…”
Section: Hasil Dan Pembahasanunclassified